2010
DOI: 10.6028/nist.ir.7753
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of refrigeration systems used for vaccine storage :

Abstract: Each year, billions of dollars of vaccines are stored in refrigerators at the facilities of a variety of medical providers. Many vaccines must be maintained in the range 2 °C to 8 °C to retain product potency. We have tested the performance of two types of refrigerators to determine if these refrigerators are suitable to this task, and to identify proper storage and temperature monitoring methods. Nineteen calibrated Type T thermocouples, distributed through the refrigerator interior, served as reference therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 1 publication
0
20
0
4
Order By: Relevance
“…During trials using the freezerless and dorm-style refrigerator models, we found that storing water bottles in the door of the unit improved overall temperature stability by reducing the impact of normal use conditions like opening the refrigerator door [1]. However, in trials of the dual-zone model, the difference in performance between the refrigerator with water bottles vs. without water bottles was less pronounced.…”
Section: Effect Of Door Opening and Closing-normal Use Simulationmentioning
confidence: 90%
See 2 more Smart Citations
“…During trials using the freezerless and dorm-style refrigerator models, we found that storing water bottles in the door of the unit improved overall temperature stability by reducing the impact of normal use conditions like opening the refrigerator door [1]. However, in trials of the dual-zone model, the difference in performance between the refrigerator with water bottles vs. without water bottles was less pronounced.…”
Section: Effect Of Door Opening and Closing-normal Use Simulationmentioning
confidence: 90%
“…Referring again to the graph, some of the thermometers attached to walls (e.g. 1,4), in close proximity to a wall (15), or hanging in the air (e.g. 7, 9) recorded large temperature spikes followed by a drop below the 2 °C limit.…”
Section: Defrost Cyclementioning
confidence: 96%
See 1 more Smart Citation
“…Weil diese erste Datenanalyse auf Schwierigkeiten beim Impfkühlschrank- und Impfstoffmanagement hindeutete, untersuchen wir diesen Aspekt in der vorliegenden Studie detaillierter. Dabei werden relevante Aspekte wie das Vorgehen bei der Impfstoffbeschaffung und -bevorratung, praxisinterne Zuständigkeiten für die Impfstoffauswahl bei der Apothekenbestellung und für die Bestandskontrolle [16,17], die Verwendung eines Ordnungssystems im Kühlschrank [16][17][18] sowie die Aufbewahrung in Originalverpackungen und in Ordnungshilfen [17,21,22] thematisiert. Außer-temperature and expiration dates, and 95 % reported vaccine storage in original card box wrappings.…”
Section: Hintergrundunclassified
“…NIST evaluated VFC cold-chain management practices in a series of studies designed to replicate everyday conditions in vaccine provider offices [2,3]. Effective vaccine storage and handling practices hinge on the use of suitable temperaturecontrolled storage cabinets, along with an accurate temperature monitoring setup capable of tracking vaccine temperature history.…”
Section: Introductionmentioning
confidence: 99%